Soil health monitoring using satellite-based remote sensors: An atlas of the Agroecology Living Lab in Tunisia - Shiri, Zahra; Le, Quang Bao (International Center for Agricultural Research in the Dry Areas, 2024)
This report explores the use of satellite-based remote sensors to monitor soil health within agroecology living landscape in Tunisia. It highlights key indicators: Normalized Difference Vegetation Index (NDVI), the Soil Moisture Index (SMI), the Normalized Difference Salinity Index (NDSI), the Soil Brightness Index (SBI), and the Bare Soil Index (BSI). This atlas of remote sensing-derived maps can enhance territorial management by identifying vulnerable zones and supporting data-driven interventions.